Immunofluorescence assay controls on untagged parasites. - Evie R. Hodgson (21866946) (2025)
(A–C) Immunofluorescence assays of TATi∆ku80 parasites lacking epitope tags (A–C, top) and epitope-tagged positive control parasites (A, B bottom, TgCIA2-mAID-HA/TgCIA1-smFP-cMyc parasites; C bottom, TgCIA1-mAID-HA/cTgCIA1WT-Ty1 parasites) were performed to test for non-specific antibody labeling in untagged parasites. Parasite samples were probed on the same day with (A) anti-HA (green) and anti-TgTom40 (magenta) antibodies, (B) anti-cMyc (green), and anti-TgTom40 (magenta) antibodies, and (C) anti-Ty1 (green) and anti-TgTom40 (magenta) antibodies using the same antibody dilutions for the negative and positive control samples. For image processing, the contrast and brightness of a positive control image of each sample was adjusted linearly, and the same adjustments (i.e., the same minimum and maximum pixel intensities) were applied to TATi∆ku80 parasites. Scale bars are 2 µm. DIC, differential interference contrast transmission image. (TIF)